The Effects of Kretek Cigarettes and Ascorbic Acid-based Vape on IL-6, TNF-α Levels, and Pulmonary Histopathology: An Experimental Study on White Rats (Rattus novergicus) on Inflammatory Response and Pulmonary Histopathology - Dora Maftikhati; Awal Prasetyo; Udadi Sadhana; Hermawan Istiadi (Faculty of Medicine, Diponegoro University, 2025)
Background: Smoking habits remain difficult to break, with 991 million smokers worldwide in 2020. Many have switched to vaping, which is regarded as safer than clove cigarettes. Exposure to cigarette smoke can increase pro-inflammatory cytokines and damage lung tissue.Objective: This study compared the effects of kretek cigarette smoke and ascorbic acid-based vape smoke on inflammatory response and lung tissue in male white rats (Rattus norvegicus).Methods: Twenty-one 8-week-old rats were randomized into three groups: control, exposed to kretek cigarette smoke, and exposed to ascorbic acid-based vape. The kretek cigarette group was exposed to smoke from 3 cigarettes/day, while the vape group received 0.5 ml/day of vape smoke, for 12 weeks. Interleukin-6 (IL-6) and Tumor Necrosis Factor-alpha (TNF-α) levels were analyzed using ELISA. The perimeter length of the alveolus, the degree of alveolar wall damage, and the extent of inflammatory cell distribution were also examined. Statistical analyses were accomplished using the ANOVA One-Way test, chi square test, and Kruskal-Wallis test.Results: Cigarette exposure significantly increased IL-6 levels (control: 8.43 ± 0.88 pg/ml; kretek cigarette: 11.45 ± 1.17 pg/ml; ascorbic acid vape: 11.83 ± 1.56 pg/ml; p = 0.000), the degree of alveolar damage (mean rank control: 6.21; kretek cigarette: 14.17; ascorbic acid vape: 11.64; p = 0.001), and the extent of inflammatory cell distribution (mean rank control: 4.00; kretek cigarette: 15.25; ascorbic acid vape: 12.93; p = 0.012). TNF-α levels increased in the kretek cigarette group, while the alveolar perimeter length increased in the ascorbic acid vape group; however, neither parameter was statistically significant (p > 0.05).Conclusion: Both kretek cigarette smoke and ascorbic acid-based vape smoke induced pulmonary inflammation and structural changes, with significant effects observed in IL-6 levels and histopathological damage, but not in TNF-α levels or alveolar perimeter length. There is a need for better regulation and increased public awareness about the dangers of smoking.